Réponses

2014-02-13T23:50:33+01:00
Bonsoir,

9x = 3(x+8)
9x = 3x + 24
9x - 3x = 24
6x = 24
x = 24/6
x = 4


3(2t + 5) = 4(5t+7)
6t + 15 = 20t + 28
6t - 20t = 28 - 15
-14t = 13
t = -13/14


2(3x + 4) - 5(1 - 2x) = 7(2x-3) + 12
6x + 8 - 5 + 10x = 14x - 21 + 12
6x + 10x - 14x = -21 + 12 - 8 + 5
2x = -12.
x = -12/2
x = -6

Meilleure réponse !
  • Utilisateur Brainly
2014-02-13T23:55:08+01:00

9x = 3x +24
9x - 3x = 24
6x = 24
x = 24/6
x = 4

3(2t + 5) = 4(5t+7)
6t + 15= 20t + 28
15-28 = 20t - 6t
-13 = 14t
t = -13/14

2(3x + 4) - 5(1 - 2x) = 7(2x-3) + 12
6x + 8 - 5 + 10x = 14x - 21 + 12
6x + 10x - 14x = -21 + 12 + 5 - 8
2x = -12
x = -6